Variation in severe postpartum hemorrhage management: A national vignette-based study. - Anne Rousseau; Patrick Rozenberg; Elodie Perrodeau; Philippe Ravaud (PLoS ONE, 2018)
OBJECTIVES:To assess variations in management of severe postpartum hemorrhage: 1) between obstetricians in the same situation 2) by the same obstetrician in different situations. STUDY DESIGN:A link to a vignette-based survey was emailed to obstetricians of 215 maternity units; the questionnaire asked them to report how they would manage the PPH described in 2 previously validated case-vignettes of different scenarios of severe PPH. Vignette 1 described a typical immediate, severe PPH, and vignette 2 a less typical case of severe but gradual PPH. They were constructed in 3 successive steps and included multiple-choice questions proposing several types of clinical practice options at each step. Variations in PPH were assessed in a descriptive analysis; agreement about management and its timing between vignette 1 and vignette 2 was assessed with the Kappa coefficient. RESULTS:Analysis of complete responses from 119 (43.4%) obstetricians from 53 (24.6%) maternity units showed delayed or inadequate management in both vignettes. While 82.3% and 83.2% of obstetricians (in vignettes 1 and 2, respectively) would administer oxytocin 15 minutes after PPH diagnosis, only 52.9% and 29.4% would alert other team members. Management by obstetricians of the two vignette situations was inconsistent in terms of choice of treatment and timing of almost all treatments. CONCLUSION:Case vignettes demonstrated inadequate management as well as variations in management between obstetricians and in different PPH situations. Protocols or procedures are necessary in all maternity units to reduce the variations in practices that may explain a part of the delay in management that leads to PPH-related maternal mortality and morbidity.